Peranan Palang Merah Indonesia Cabang Yogyakarta pada Masa Perang Kemerdekaan II di Yogyakarta, 1948-1949 - Muchamad Triyanto; Bambang Eka Saputra; Abdul Hafiz; Zidni Zidni; Suhupawati Suhupawati (Universitas Hamzanwadi, 2024)
This study aims to reveal the crucial role of the Yogyakarta Branch of the Indonesian Red Cross (PMI) during the Second War of Independence, particularly in the 1948-1949 period when Yogyakarta became one of the centers of battle and Dutch military aggression. This research is highly relevant, considering that during this period, the Indonesian nation was at the height of its struggle to defend its independence, which had been proclaimed on August 17, 1945. Specifically, the second military aggression launched by the Dutch on December 19, 1948, caused widespread chaos in Yogyakarta, affecting both the Indonesian National Army (TNI) and civilians. Using historical research methods, which include the stages of heuristics, source criticism, interpretation, and historiography, this study reveals the significant contribution of PMI in its humanitarian mission during the conflict. The Yogyakarta Branch of PMI played a vital role in providing medical aid, treating wounded victims, and organizing public kitchens for fighters and civilians affected by the war. PMI not only assisted the TNI on the battlefield but also supported civilians who became victims of Dutch attacks. Through its efforts, PMI contributed to defending Indonesia’s independence by carrying out critical humanitarian activities during the war, making them an integral part of the nation's struggle.